Analisis Deflectometry Dan Overlay Metode Bina Marga 2017 Pada Jalan SM Amin Kota Pekanbaru - Bagus Muhammad Akbar; Elianora Elianora; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Road is one of transportation infrastructure which has very important role in economic growth in rural or urban areas. SM Amin Road is located in Payung Sekaki District and this road is an arterial road that has 2 track and 6 lanes. SM Amin road has length of 8.14 km and widthof 8 m. The road was previously overlayed in 2016 because the road was damaged such as swelling, potholes, and cracks. At present (2019) the road is damaged again so that it could be dangerous for road users. This study analyzed deflectometry result from benkelman beam. Theresults reveal that the subgrade is in poor condition. The condition was analyzed using 2017 Bina Marga Method, it shows that overlay is required along STA 03+900 until 05+200 with the thickness of 11 cm. The results of the deflectometry analysis shows that Jalan SM Amin hasa poor subgrade, so it is necessary to be improved. However, handling using structural overlays according to the 2017 Bina Marga Method can be used to reduce the stress which received bythe subgrade so that it can minimize the cost of pavement repair.Keywords: 2017 Bina Marga Method, Benkelman Beam, Deflection, Deflectometry, Overlay